Corrosion-fatigue: a review of damage tolerance models. (4th July 2018) - Larrosa, N. O.; Akid, R.; Ainsworth, R. A.
ABSTRACT: The synergistic combination of mechanical fatigue stresses and environmental agents acting together can be more detrimental than that of the summation of the contributions of each mechanism acting separately. Major attempts to understand the contribution of the different agents (microstructure, chemical composition of environment, temperature, loading conditions, etc.) have been reported in the literature. Nevertheless, current knowledge is insufficient to address life estimation with a sound physical basis from the initiation of localised corrosion (such as pitting) to the estimation of crack propagation. Major simplifications and assumptions have been required in the development of life prediction methodologies. This paper reviews recent efforts made by the different interested parties, in both academia and industry, in the development of corrosion fatigue (CF) lifetime prediction procedures. The paper mainly focuses on the methodologies proposed in the literature for oil and gas, nuclear, energy generation and aerospace applications, dealing with pitting CF damage in aluminium alloys, carbon and stainless steels. The transition of a pit into a small crack (SC) and its growth is influenced by the interaction of the pit stress/strain concentration and the local environmental conditions, making the modelling of this stage of the utmost complexity. A major trend in the models reviewed in this paper is to simplify the analysis by assuming the pit (a volumetric defect) as a sharp crack, decouple the CF problem and account for the mechanical and environmental contributions separately. These procedures heavily rely on fitting experimental data and exhibit low generality in terms of application to varying system conditions. There is a clear opportunity in this field to develop mechanistically based methodologies, considering the inherent dependence of the damage mechanism on the interaction of environmental, metallurgical and mechanical features, allowing more realistic lifetime estimates and defect tolerance arguments, where pit-to-crack transition and SC initiation stages pose a significant challenge. Abbreviation: ASME: American Society of Mechanical Engineers; API: American Petroleum Institute; BP: British Petroleum; BS: British Standards; BWR: Boiling Water Reactor; CF: Corrosion fatigue; DNV: Det Norske Veritas; FCGR: Fatigue crack growth rate; FCI: Fatigue crack initiation; FCP: Fatigue crack propagation; FFS: Fitness for service; HA: Hydrogen assisted; HRR: Hutchinson, Rice and Rosengren stress fields; LC: Long crack; LEFM: Linear Elastic Fracture Mechanics; S-N: Stress vs. number of cycles